Analyzing Customer Satisfaction Using Importance Peformance Analysis (IPA) on 19 Liter Packaging Drinking Water Products: Menganalisa Kepuasan Pelanggan Menggunakan Importance Peformance Analysis (IPA) Terhadap Produk Air Minum Dalam Kemasan (AMDK) 19 Liter - Ningsih, Indrawati Rahayu; Jakaria , Ribangun Bamban (Procedia of Engineering and Life Science, 2023)
Bottled drinking water is water that has been processed without additives and then packaged and safe for consumption. Bottled bottled products also vary widely, ranging from 250 ml packages to products with 19 liter packaging. This 19 liter bottled water product is the one most widely used by the public where it is not only consumed as drinking water but also used as a medium for cooking. In addition to the affordable price, this package also contains quite a lot of water compared to other packages so that it is able to meet daily needs. So that is what has resulted in various brands of bottled water products starting to emerge. This research uses the importance performance analysis (IPA) method. Data collection was carried out by observing and distributing questionnaires. the results of the study indicate that there are 8 (eight) attributes that require improvement and 3 (three) attributes that canlowered the level of service to save costs and effort in order to meet the level of satisfaction with consumers.